Catalogue and bibliography of Recent and fossil Botula (Bivalvia: Mytilidae) - Kleemann, Karl (Zootaxa, 2007)
This annotated catalogue considers the names for species, subspecies and varieties of Recent and fossil bivalves that have been used for mytilid Botula Mörch, 1853, as a genus or subgeneric taxon in the literature or that are given herein for the first time. Information about types, including collection numbers, sizes, localities and geological ages are included when available. A bibliography with annotated listing of synonymies and chresonymies is presented for each of the about 50 names. The respective geographic and geologic distributions are summarized. A single-species concept for this group, put forward by earlier authors, is discussed. References to species as Botula, but now placed in other genera, are listed and discussed. The geological record for Botula begins at least in the Cretaceous.